HUBUNGAN BERAT BADAN LAHIR BAYI DENGAN KEJADIAN RUPTURE PERINEUM PADA PERSALINAN NORMAL DI RSUD PROF. DR. W. Z JOHANNES KUPANG - Trimurdani Semsi,; Ni Ketut Somoyani,; Ni Nyoman Suindri, (Journal of Innovation Research and Knowledge, 2025)
Perineal rupture is one of the most common complications in normal labour. Infant birth weight is thought to play a role in determining the severity of perineal rupture. This study aims to analyse the relationship between baby's birth weight and the incidence of perineal rupture in mothers giving birth at RSUD Prof. Dr. W. Z Johannes Kupang. Observational research method with cross-sectional design, 46 respondents. Using secondary data with Spearman Rank statistical test. The results of the study were the majority of babies had normal birth weight (2500-4000 grams) by 73.9%, . Most mothers experienced grade 2 perineal rupture (60.9%). Analysis showed a significant association between infant birth weight and the incidence of perineal rupture (p-value = 0.001). Normal birth weight infants were more likely to cause grade 2 ruptures than low birth weight infants, who generally only cause grade 1 ruptures. The conclusion in this study is that infant birth weight affects the severity of perineal ruptures in normal labour. Infants with normal birth weight are more at risk of causing moderate perineal rupture